Release behavior of 1‐methylcylopropene coated paper‐based shellac solution in response to stepwise humidity changes to develop novel functional packaging for fruit. Issue 10 (10th July 2019) - Ariyanto, Hermawan Dwi; Chiba, Makoto; Oguma, Keisuke; Tatsuki, Miho; Yoshii, Hidefumi
Abstract : 1‐Methylcyclopropene (1‐MCP) has been shown to be a suitable inhibitor of ethylene production in fruit and vegetables during preservation and distribution. In this study, a 1‐MCP controlled‐release system on coated paper was produced using shellac as the coating material. The effect of humidity and temperature on the release of 1‐MCP from the coated paper was investigated using a dynamic sorption system (DVS) with stepwise humidity changes (initial 20% relative humidity (RH) for 2 h, then increased to 40%, 50%, 60%, and 80% RH for 2 h, respectively). The release rate kinetic data were simulated using an Avrami equation with a mechanism release number n of 1.26. The results showed that the dynamic release of 1‐MCP from the coated paper was mainly affected by humidity, for which the release rate constant could be correlated with moisture concentration in humid air. The highest humidity condition (80% RH) resulted in the highest apparent activation energy of 46.8 kJ/mol. The effect of 1‐MCP coated paper on apple storage was evaluated by measuring the ethylene production rate, flesh firmness, and titratable acidity (TA) of apple. Ethylene production rates of apple were significantly affected with 1‐MCP coated paper. The values were 0.22 nL/g FW/h at 50 mg of 1‐MCP powder and 44.7 nL/g FW/h at 0 mg of 1‐MCP powder after 15 days at 4°C and 15 days at 20°C. The other properties of apple such as flesh firmness and TA also indicated that 1‐MCP coated paper could delay fruit softening during storage time. Based on these results, the release of 1‐MCP could be controlled by coating paper with shellac solution and promising to produce functional packaging for fruit. Abstract : The additional of 1‐MCP inclusion complex in a coated paper by shellac solution can prevent and inhibit the ethylene action during postharvest processing. It will be useful to prolong the shelf life of fruits by delaying the ripening process. The release behavior of 1‐MCP from coated paper was important to develop functional packaging.